Impacto da morfologia urbana nas condições térmicas internas e externas de habitações de interesse social: acoplamento entre ENVI-met e EnergyPlus - Apolinário, Bruna de Souza (Universidade Federal de São Carlos, 2025)
Amid global warming, the increasing occurrence of heat waves, and the urban heat island effect, exploring solutions to mitigate human thermal stress and energy demand for cooling becomes essential. In this context, urban planning that considers morphology indices aligned with the climate contributes to improving both external and internal thermal conditions of housing. Based on these issues, this study aims to analyze the external and internal thermal conditions of social housing units in relation to verticality and built typologies, both during and outside a heat wave. To achieve this, scenarios were developed with three housing typologies: single-story houses, H-shaped towers, and courtyard buildings. Multifamily housing was analyzed at two heights: 14 and 29 meters. The methodology was based on the collection of microclimatic data and computational simulations. The scenarios were simulated using the ENVI-met software, with the collected data used as input. The microclimatic data from these simulations were subsequently coupled to EnergyPlus using the chaining method and the BCVTB software. The results highlighted the high levels of thermal stress to which social housing residents are exposed during heat waves, which can cause heat cramps, exhaustion, and heatstroke, negatively affecting health and well-being. Additionally, it was found that scenarios with courtyard buildings performed best externally, being the only ones to provide areas without extreme thermal stress. However, internally, they generated the highest levels of thermal stress and energy demand for cooling, with a 29.22% increase. On the other hand, H-shaped towers, despite presenting less favorable external thermal conditions compared to courtyard buildings, achieved the best internal results. These scenarios were the only ones without internal thermal stress levels classified as "at risk" and reduced cooling energy demand by 20.97% compared to single-story houses. Regarding building height, the reduction proved advantageous during the heat wave but unfavorable outside this period. These results highlight the impact of housing typologies and building height on thermal stress levels and energy demand for cooling. However, they indicate that while an urban configuration may improve external thermal conditions, it may worsen internal conditions. Therefore, it is essential to deepen studies on the impact of urban morphology on the indoor thermal environment of housing to support urban planning that minimizes both energy consumption and external and internal thermal stress.
Impact of urban morphology on the internal and external thermal conditions of social housing: coupling between ENVI-met and EnergyPlus
Keywords: Morfologia urbana; Planejamento urbano; Resiliência climática; Edifícios pátios; Acoplamento; Urban morphology; Urban planning; Climate resilience; Courtyard buildings; Coupling; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PROJETO DE ARQUITETUTA E URBANISMO::PLANEJAMENTO E PROJETO DO ESPACO URBANO; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PROJETO DE ARQUITETUTA E URBANISMO::PLANEJAMENTO E PROJETOS DA EDIFICACAO; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::TECNOLOGIA DE ARQUITETURA E URBANISMO::ADEQUACAO AMBIENTAL